2021
DOI: 10.7554/elife.69708
|View full text |Cite
|
Sign up to set email alerts
|

Genetic depletion studies inform receptor usage by virulent hantaviruses in human endothelial cells

Abstract: Hantaviruses are RNA viruses with known epidemic threat and potential for emergence. Several rodent-borne hantaviruses cause zoonoses accompanied by severe illness and death. However, assessments of zoonotic risk and the development of countermeasures are challenged by our limited knowledge of the molecular mechanisms of hantavirus infection, including the identities of cell entry receptors and their roles in influencing viral host range and virulence. Despite the long-standing presumption that β3/β1-containin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
2
16
0
1
Order By: Relevance
“…Thus, F83L reduces PCDH1 binding to both ANDV and SNV Gn/Gc, but abolishes PCDH1 binding only to SNV Gn/Gc, concordant with its selective effect on entry and infection (Figure 1F). As shown previously, PCDH1 is dispensable for viral infection mediated by Old World hantavirus Gn/Gc (e.g., HTNV) (Figure 1F) (6,7). These findings, together with the conservation of F83 in PCDH1 orthologs from species known to be susceptible to New World hantaviruses (Figure 1C), provide evidence that Gn/Gc:PCDH1 recognition can influence the cellular host range of hantaviruses.…”
Section: Pcdh1 Sequence Variation At Residue 83 Influences Endothelia...supporting
confidence: 79%
See 3 more Smart Citations
“…Thus, F83L reduces PCDH1 binding to both ANDV and SNV Gn/Gc, but abolishes PCDH1 binding only to SNV Gn/Gc, concordant with its selective effect on entry and infection (Figure 1F). As shown previously, PCDH1 is dispensable for viral infection mediated by Old World hantavirus Gn/Gc (e.g., HTNV) (Figure 1F) (6,7). These findings, together with the conservation of F83 in PCDH1 orthologs from species known to be susceptible to New World hantaviruses (Figure 1C), provide evidence that Gn/Gc:PCDH1 recognition can influence the cellular host range of hantaviruses.…”
Section: Pcdh1 Sequence Variation At Residue 83 Influences Endothelia...supporting
confidence: 79%
“…Virus-receptor interactions can influence viral entry, cell and tissue tropism, viral host range and pathogenesis, and afford attractive targets for antiviral countermeasures (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). We previously demonstrated that PCDH1 is an essential entry host factor for New World hantaviruses (6,7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant vesicular stomatitis viruses rVSVs expressing enhanced green fluorescent protein (eGFP) and bearing Gn/Gc from HTNV, SEOV, DOBV, ANDV, SNV, CHOV, and VSV G were engineered, rescued, and propagated following published protocols (30,31,(47)(48)(49). rVSV carrying a phosphoprotein P fused to mNG and bearing PUUV Gn/Gc has been described previously (29).…”
Section: Cell Linesmentioning
confidence: 99%